Introduction of PCR testing reveals a previously unrecognized burden of yersiniosis in Hampshire, UK - Clarke, Mattea; Dabke, Girija; Strakova, Lenka; Jenkins, Claire; Saavedra-Campos, Maria; McManus, Oliver; Paranthaman, Karthik (Journal of medical microbiology, 2020)
Current testing practices for yersiniosis mean that its true incidence and epidemiology are not well understood. In mid-2016, the introduction of testing via a multiplex gastrointestinal PCR panel at Portsmouth hospital laboratory in Hampshire, UK, resulted in a marked increase in the number of cases identified locally. Here we describe the epidemiology and microbiology of cases identified at Portsmouth laboratory following the introduction of PCR testing. A case was defined as a person with a stool specimen in which was detected by PCR and/or culture at Portsmouth NHS Trust laboratory between 1 January 2014 and 31 December 2018. A case list was created from laboratory data submitted by Portsmouth laboratory to Public Health England (PHE), updated with speciation and serotyping data from the PHE reference laboratory. Descriptive analysis was performed. Over 30 months following introduction of PCR testing, 199 cases were confirmed with , compared to two cases in the preceding 30 months. This corresponds to a rate of 13.8 and 0.1 per 100 000 population per year respectively ( <0.0001). In total, 85% of tested isolates were , belonging to multiple serotypes, and the rest belonged to a range of -like species. Introduction of PCR testing led to the identification of a previously unrecognized burden of yersiniosis in Hampshire. The diversity of species and serotypes suggests heterogeneity in sources and transmission routes. Further research on exposures, risk factors and clinical sequalae is needed to improve our understanding of the clinical and public health impact.